Green Project Chemistry Based Learning Model to Enhance Scientific Literacy And Sustainability Awareness In Education - Daulay, Rabiah Afifah; Gea, Olivia Febriana; Daeli, Dinastini; Sinaga, Husna Khoiri; Manalu, Jenny Teresa; Panggabean, Tiara (LAVOISIER: Chemistry Education Journal, 2025)
Green chemistry education has become a significant approach in improving students' scientific literacy and sustainability awareness. This study examines the application of project-based learning (PjBL) model in the context of green chemistry as an innovative method to strengthen students' understanding of sustainability principles. Through literature review from various scientific sources, this study shows that the integration of PjBL in green chemistry learning can improve students' critical thinking, collaboration, and communication skills. In addition, project-based learning allows students to engage in more environmentally friendly experiments, such as the development of biodegradable materials and chemical waste management strategies. However, the implementation of this method still faces challenges, such as limited understanding of educators about green chemistry, lack of resources, and suboptimal integration into the curriculum. Therefore, intensive training is needed for educators, provision of comprehensive learning materials, and utilization of technology as a tool. With the right support, the implementation of this model can produce a generation that is more environmentally aware and able to provide solutions to global sustainability challenges.